R3f Enterprise: Drill & Tap (renovation) / Muhammad Raziq Jamaludin, Muhammad Fahmy Abd Aziz, Muhammad Farid Asyraf Salim, Muhammad Farid Izzudin Abdul Latif - Jamaludin, Muhammad Raziq; Abd Aziz, Muhammad Fahmy; Salim, Muhammad Farid Asyraf; Abdul Latif, Muhammad Farid Izzudin (2017)
Basically, the nature of this business is focused on the workshop specialization. Our business buys raw materials then converts them into finished goods then sells them to customers at a certain price.